Evaluasi Pengalaman Pengguna Pada Aplikasi Shopee Menggunakan Metode User Experience Questionnaire (UEQ) - Fajar Fina Alawiyah; Dila Seltika Canta (Journal of Information System Research (JOSH), 2022)
The development of technology in the current era has attracted the attention of many people to make this a business area, namely online business. This is related to the increasing need for information and the effectiveness of online shopping services that are more attractive, easier and profitable for consumers. Online shopping sites can be accessed through applications that are already installed on consumer mobile phones (Android, IOS, Windows Phone). This study aims to find out about the experience of shopee application users in becoming an online shopping tool for many people and can find out which user experience suits the user both from the convenience, function and ease of using the shopee. This study provides a comparison through a user experience questionnaire (UEQ) which has six aspects of assessment, including attractiveness, sharpness, efficiency, dependence, stimulation, and novelty. The UEQ questionnaire distributed to 54 respondents, the results of the UEQ questionnaire show that respondents have a positive impression of the Shopee application as a means of online shopping where the survey results have positive values ​​(having a mean value > 0.8).